Peripheral tuberculin purified protein derivative specific T cell immunoreactivity dynamics in non-muscle invasive bladder cancer patients receiving bacillus Calmette-Guerin instillation treatment - Duan, Huangqi; Xia, Weimin; Xu, Ding; Chen, Yingying; Ding, Yu; Wang, Chen; Sun, Ruiming; Yao, Chengcheng; Zhang, Shun; Wu, Yu; Ji, Ping; Wang, Shujun; et al. (Frontiers in Oncology, 2022)
Intravesical bacillus Calmette-Guerin (BCG) instillation is recommended as an adjuvant therapy for intermediate-risk and high-risk non-muscle invasive bladder cancer (NMIBC) after transurethral resection of bladder tumor (TURBt) with nearly 70% reoccurrence. In the present study, we investigated the dynamics of peripheral purified protein derivative (PPD)-specific immune responses along the treatment. Intravesical BCG instillation caused a significant increase in peripheral PPD-specific IFN-γ release of NMIBC patients, when compared to those receiving chemo-drug instillation. Through a follow-up study, we detected rapid increase in PPD-specific IFN-γ, IL-2, and IL-17A producing CD4+ and CD8+ T cells in the induction phase. Interestingly, the frequencies of PPD-specific IFN-γ and IL-2 producing CD4+ and CD8+ T cells decreased dramatically after induction treatment and were restored after BCG re-instillation, whereas IL-17A-producing T cells remained at the maintenance phase. However, we only observed that the percentages of peripheral CD8+ T cells were significantly higher in BCG responder patients than those in BCG refractory patients at the baseline with the potential of predicting the re-occurrence. A more dramatic increase in PPD-specific IFN-γ and IL-2 producing CD4+ and CD8+ T cells after one and two dose BCG instillations was observed in refractory NMIBC patients. Therefore, regional BCG instillation induced transient peripheral PPD-specific T cell responses, which could be restored through repetitive BCG instillation. Higher proportions of peripheral CD8+ T cells at baseline were associated with better responses to BCG instillation for the prevention of reoccurrence of bladder cancer.